Online Learning Evaluation and Student Satisfaction in Islamic Religious Education Distance Programs - Syaikhu Muhamad; Tamsik Udin; Suklani (Ilmu Inovasi Nusantara, 2026)
The shift from face-to-face instruction to online learning has introduced significant challenges in maintaining student satisfaction, particularly in Islamic Religious Education (PAI) courses. Issues such as limited interaction, unclear academic information, restricted access to academic services, and perceptions of tuition fees during distance learning have raised concerns regarding the effectiveness of online learning implementation. Student satisfaction is a crucial indicator of learning quality and plays an important role in achieving the educational objectives of PAI programs. This study aims to examine the impact of online learning on student satisfaction among third-semester students enrolled in the Distance Learning Program (PJJ) of Islamic Religious Education at IAIN Syekh Nurjati Cirebon. Specifically, the study examines the impact of online learning evaluation on student satisfaction, while also identifying other factors that contribute to it. A quantitative research approach was employed using regression analysis. Data were collected through a structured questionnaire distributed to third-semester PJJ students, measuring variables such as online learning evaluation, clarity of academic information, accessibility of academic staff, and perceptions of tuition fees. The results indicate that the constant has a significant effect on student satisfaction (coefficient = 24.125, p < 0.05), whereas the online learning evaluation variable does not have a statistically significant effect (coefficient = 0.011, p > 0.05). Despite the non-significant influence of learning evaluation, other factors—particularly clarity of information, tuition fee structure, and staff accessibility—were found to meaningfully contribute to student satisfaction. These findings suggest that improving the clarity of academic communication, reviewing tuition fee policies, and enhancing the accessibility of academic and administrative services are crucial strategies for enhancing student satisfaction. Such improvements can support the development of more effective and sustainable online learning practices within Islamic Religious Education programs